2015
DOI: 10.1371/journal.pntd.0004095
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in Rio Grande do Sul, Brazil: An Ecosystem Approach in the Animal-Human Interface

Abstract: BackgroundLeptospirosis is an epidemic-prone neglected disease that affects humans and animals, mostly in vulnerable populations. The One Health approach is a recommended strategy to identify drivers of the disease and plan for its prevention and control. In that context, the aim of this study was to analyze the distribution of human cases of leptospirosis in the State of Rio Grande do Sul, Brazil, and to explore possible drivers. Additionally, it sought to provide further evidence to support interventions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 29 publications
2
60
0
17
Order By: Relevance
“…The disease among the city residents was often associated with work in rural areas (suburban areas). The world literature also confirmed that the disease prevalence (2008)(2009)(2010)(2011)(2012) among the rural population of Brazil was 8 times higher than in urban areas [22]. At the same time, according to data from other countries, there is a trend to greater involvement of the urban population in the epidemic process [23], especially in adverse sanitary conditions -high water, contact with sewage, etc.…”
Section: Resultsmentioning
confidence: 90%
“…The disease among the city residents was often associated with work in rural areas (suburban areas). The world literature also confirmed that the disease prevalence (2008)(2009)(2010)(2011)(2012) among the rural population of Brazil was 8 times higher than in urban areas [22]. At the same time, according to data from other countries, there is a trend to greater involvement of the urban population in the epidemic process [23], especially in adverse sanitary conditions -high water, contact with sewage, etc.…”
Section: Resultsmentioning
confidence: 90%
“…De acordo com Schneider et al (2015) as populações rurais do Rio Grande do Sul, têm cerca de oito vezes maior risco de contrair leptospirose do que as populações urbanas, e os casos rurais estão principalmente em duas zonas, caracterizadas pela maior produção de tabaco (região central) e maior produção de arroz (região sul).…”
Section: Animais Domésticos E a Leptospira Em Populações Ruraisunclassified
“…Um estudo realizado por Barcellos et al (2003) de casos notificados em Pelotas no Rio Grande do Sul, apresentou uma incidência de 16,3 casos por 100 mil habitantes, uma frequência superior à média nacional de 3,5 casos por 100 mil habitantes. Já Schneider et al (2015), também sobre casos notificados no Rio Grande do Sul, indicam uma incidência de 1,2 a 2,4 casos para cada 10 mil habitantes no município de Pelotas. A associação entre os trabalhadores da cultura do arroz e a leptospirose já foi descrita na literatura (CAMINITI et al, 2011;WHO, 2003).…”
Section: Animais Domésticos E a Leptospira Em Populações Ruraisunclassified
See 1 more Smart Citation
“…Leptospirosis is an infectious disease that requires the study of human–animal–environment interface, based on the One health concept (Schneider et al., ). The pathogen is transmitted by exposure to contaminated water or urine from infected animals and may survive for days to months in freshwater, soil or mud (Rood, Goris, Pijnacker, Bakker, & Hartskeerl, ).…”
Section: Introductionmentioning
confidence: 99%